GE_GERICHTE C/19822/2005 vom 3. September 2014 - GE Cour de justice (2014)
CURATELLE; CONFLIT D'INTÉRÊTS; APPROBATION(EN GÉNÉRAL); QUALITÉ POUR RECOURIR; APPLICATION RATIONE TEMPORIS; AMENDE | LaCC.35; CC.450.2; CC.403.1; CC.408.1; CPC.128.3; aCC.392; aCC.421; aCC.422